A questionnaire based comparative study on dry lab versus wet lab among second year medical undergraduates in a tertiary care hospital of Bihar - Kumar, Mukesh; ., Soni; Singh, Dheeraj Kumar; Kumar, Sunil; Kumar, Subodh (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Objective of the study was to identify whether there is any benefit of integrating dry lab/computer assisted lab (CAL) tool with conventional teaching/wet lab in experimental part of pharmacology. Methods: A questionnaire based study was conducted among 158 second year medical undergraduates in the department of pharmacology. The questionnaire was distributed among students with proper prior instructions in practical class. Students willing to participate in the study were included. Results: Total 94.9% were in the favour of replacing conventional teaching with CAL lab learning, 74.7% felt conventional lab to be more complex, 92.4% has the opinion of CAL lab result has less error along with that majority student felt it to be less time consuming, need lesser assistance and enhance learning. 67% student also felt real experimentation can’t be learned by CAL tool and 83.5% have their thought that CAL lab can never help them in exercising real experiment. Conclusions: Although there is no substitution of conventional teaching methods, in this new era of information and technology CAL lab can be the saviour to students in making better understanding and enhancing the performance without help of experimental animals.